Spyridon Zambelios and the demand for Realism in Greek literature - Πολυχρονάκης, Δημήτρης (Ariadne, 2021)
THE purpose of this paper is to demonstrate that the literary controversy between realism and romanticism in 19th century Europe is the product of a deeper complicity between the two, which made them communicating vessels. In the area of Modern Greek criticism, Spyridon Zambelios is a typical example of such complicity: despite the fact that he was the most prominent romantic historian of Greece, he was also the person who introduced the concept of realism in Greek philology as the antidote to the idealism of romanticism. More specifically, Zambelios invoked the values of realism in 1860, attacking the romantic poetry of Dionysios Solomos. However, my main argument is that Zambelios’ realism is compatible with his romanticism and, what is more, it stems from the latter. What Zambelios names ‘realism’ is in fact the product of an advanced idealism that attempts to rationalize the historical reality according to the standards of Hegel’s philosophy of history.